Easy Spanish step-by-step - Bregstein, Barbara (McGraw Hill-Ascent Audio, 2021)
Easy Spanish Step-by-Step is THE top-selling Spanish book on all of Amazon! Ranked #1 in the Spanish Language Instruction category after more than 5,000 4- and 5-star reviews, the reviews speak for themselves. Now, it's your turn to learn Spanish with us! This audio course is designed to help you learn Spanish as quickly and as thoroughly as possible. No one wants to spend effort and hours learning a language, and still not truly, authentically, be able to speak it. Well - no se preocupe ("don't worry") - with years of experience and thousands of success stories, we've got you covered! No matter your reason, once you've committed yourself to learning this beautiful language, you want to be sure you do it right. Right? Here's what you can expect from your Easy Spanish Step-by-Step course: - Be ready to listen and speak - a lot! This is the way that each and every one of us learned our first language, and the number one way that our brain actually learns and remembers information. You will be speaking Spanish out loud within your first few minutes with us. - Learn correct grammar and be able to apply it to your communication. This audio course is the product of a fusion of two methods: comprehensive grammatical understanding blended with authentic, child-like acquisition through listening and speaking. - Actively engage in your learning with dynamic practice activities! This course is not a podcast or a lecture to simply listen to. You are going to be interacting with us the entire time: responding to questions, filling in the missing word, giving your opinions, and more. - Tune your 'Spanish ear' to an authentic, native Spanish-speaker accent. Your new Spanish teacher, Rachel, is accompanied by Jorge, a native Spanish speaker. Adapt your listening skills to the "real" Spanish you will hear out in the community and across the world - not only the slow, clearly-enunciated Spanish you would hear in a classroom setting. - Make meaningful connections between newly introduced words and concepts and your own life, further increasing your brain's ability to remember them thanks to the personal connection. - Develop your skills through a natural mix of language structure and fluid, conversational-style listening. - Listen to original stories and poems in Spanish and demonstrate understanding through interactive questions. - Receive consistent encouragement to recognize your growth, and to always take the course at your own pace. Easy Spanish Step-by-Step is designed in such a way that each section builds upon the last to help your brain progressively create lasting and meaningful connections to each new word and grammar concept. Simply by listening and speaking out loud with us, you will naturally progress, step-by-step, toward Spanish communication and fluency